2016
DOI: 10.1016/j.eurpsy.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

What is the minimal dose of cognitive behavior therapy for psychosis? An approximation using repeated assessments over 45 sessions

Abstract: Our findings support recommendations to provide CBTp over a minimum of 16 sessions and indicate that these recommendations are generalizable to clinical practice settings. However, the findings also imply that 25 sessions are the more appropriate dose. This study contributes to an empirically informed discussion on the minimal and optimal dose of CBTp. It also provides a basis for planning randomized trials comparing briefer and longer versions of CBTp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
1
26
1
2
Order By: Relevance
“…As therapists were often the only mental health professionals involved in the client’s care, it frequently became therapists’ responsibility to address these issues, and, therefore, the length of therapy should be interpreted in this context. Further, given that the NICE guidelines recommend (even when treated in isolation) at least 12 sessions for PTSD, with more for complex PTSD or multiple traumas (23), and at least 16 for psychosis (22) and for severe depression (79), in addition to the recent finding that 25 sessions is the optimal dose for CBT for psychosis (80), 41 sessions is perhaps understandable for this very complex client group. However, whether the stabilisation phase is necessary remains an empirical question that needs to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…As therapists were often the only mental health professionals involved in the client’s care, it frequently became therapists’ responsibility to address these issues, and, therefore, the length of therapy should be interpreted in this context. Further, given that the NICE guidelines recommend (even when treated in isolation) at least 12 sessions for PTSD, with more for complex PTSD or multiple traumas (23), and at least 16 for psychosis (22) and for severe depression (79), in addition to the recent finding that 25 sessions is the optimal dose for CBT for psychosis (80), 41 sessions is perhaps understandable for this very complex client group. However, whether the stabilisation phase is necessary remains an empirical question that needs to be tested.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of dose‐response studies found that adequate dose recommendations varied according to clinical populations and methodological approach (Robinson, Delgadillo, & Kellett, 2020). For example, patients with psychosis required 8–30 sessions of high‐intensity cognitive‐behavioral therapy (CBT) (Falkenström, Josefsson, Berggren, & Holmqvist, 2016; Lincoln, Jung, Weisjahn, & Schlier, 2016), while patients with mild‐to‐moderate anxiety and depression required only 4–6 sessions of low‐intensity CBT (Delgadillo et al, 2014; Delgadillo, Kellett et al, 2016). Furthermore, studies using more or less conservative definitions of treatment response yield different conclusions (Anderson & Lambert, 2001; Asay, Lambert, Gregersen, & Goates, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, conclusions from meta-analytic reviews suggest that, when considered at the group level, CBT may be less effective than initially thought (Laws, Darlington, Kondel, McKenna, & Jauhar, 2018 (Lincoln et al, 2016). However, although the overall pattern of results is encouraging, they also make it abundantly clear that not all clients benefit-at least, not from this particular form of brief-cognitive behavioural therapy for distressing voices.…”
Section: Validity Of the Clinical Significance Classificationsmentioning
confidence: 99%
“…Similarly, in view of the limited funding of healthcare services, tracking clinically significant change can assist services to provide an optimal "dose" of therapy sessions that generates individual benefit (i.e., with no more sessions than is necessary; Lincoln et al, 2016). For example, in the context of a transdiagnostic service like Perth Voices Clinic, an important question to ask is whether the number of individuals benefiting from cognitive behavioural therapy varies by diagnostic category (e.g., is there a difference in the benefits for clients with psychotic disorder, versus those with mood disorder or post-traumatic stress disorder?).…”
Section: Validity Of the Clinical Significance Classificationsmentioning
confidence: 99%
See 1 more Smart Citation